2020
DOI: 10.1021/acssensors.0c01742
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Test for Fast Detection of SARS-CoV-2 in Nasal and Throat Swabs

Abstract: Mass testing is fundamental to face the pandemic caused by the coronavirus SARS-CoV-2 discovered at the end of 2019. To this aim, it is necessary to establish reliable, fast, and cheap tools to detect viral particles in biological material so to identify the people capable of spreading the infection. We demonstrate that a colorimetric biosensor based on gold nanoparticle (AuNP) interaction induced by SARS-CoV-2 lends itself as an outstanding tool for detecting viral particles in nasal and throat swabs. The ext… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
188
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(192 citation statements)
references
References 37 publications
2
188
0
2
Order By: Relevance
“…The test results showed that the colorimetric biosensor was able to detect a very low amount of target proteins, and its limit of detection was very close to that of the real-time PCR method. Therefore, this colorimetric detection platform’s limit was reported based on the real-time PCR cycle threshold (Ct) and was C t = 36.5 [ 51 , 52 ].…”
Section: Biomarkers and Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results showed that the colorimetric biosensor was able to detect a very low amount of target proteins, and its limit of detection was very close to that of the real-time PCR method. Therefore, this colorimetric detection platform’s limit was reported based on the real-time PCR cycle threshold (Ct) and was C t = 36.5 [ 51 , 52 ].…”
Section: Biomarkers and Indicatorsmentioning
confidence: 99%
“…The functionalized AuNPs were dispersed on the sensor surface to enhance the binding events. SARS-CoV-2 spike protein 4.2 fmol Colorimetric biosensor based on localized surface plasmon resonance (LSPR) [ 51 ] AuNPs were used in these biosensors because of their surface chemistry and biocompatibility. By using gold nanoparticles in the colorimetric method, the color changes from red to blue in a colloidal suspension because of LSPR coupling among the AuNPs, which were functionalized with antibodies SARS-CoV-2 spike, envelope, and membrane proteins C t = 36.5 (the limit of detection of this colorimetric biosensor was reported based on the real-time PCR cycle threshold (Ct)) Gold nano spikes in an opto-microfluidic chip (based on localized surface plasmon resonance) [ 53 ] 1000 Å of Gold was electrodeposited on a 50 Å of chromium layer on the glass substrates.…”
Section: Biomarkers and Indicatorsmentioning
confidence: 99%
“…RT-LAMP technologies and variants of such (i.e. coupled with colorimetry) have been gaining attention as strong potential alternative detection methods as they are faster and cheaper due to the elimination of the RNA extraction step in conventional PCR ( Dao Thi et al, 2020 ; Lalli et al, 2020 ; Ventura et al, 2020 ). However, as with any other nucleic acid-based tests, specific primers are still needed and in the event of virus mutation, these particular primers must be redeveloped to be able to detect mutated strains.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis using this method can be achieved within 15 min at 88.66% with a specificity of 90.63% [ 241 ]. A colorimetric method using Au NPs was also reported [ 242 ]. The analysis takes place in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…The detection of these proteins depends on the red-shifted SPR peak of Au NPs. The analysis requires few minutes [ 242 ]. These methods offer high sensitivity, selectivity and needed short analysis time (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%